VcRR2 regulates chilling-mediated flowering through expression of hormone genes in a transgenic blueberry mutant. Issue 1 (21st August 2019) - Lin, Tianyi; Walworth, Aaron; Zong, Xiaojuan; Danial, Gharbia H; Tomaszewski, Elise M; Callow, Pete; Han, Xiumei; Irina Zaharia, L; Edger, Patrick P; Zhong, Gan-yuan; Song, Guo-qing
Abstract: The molecular mechanism underlying dormancy release and the induction of flowering remains poorly understood in woody plants. Mu-legacy is a valuable blueberry mutant, in which a transgene insertion caused increased expression of a RESPONSE REGULATOR 2 -like gene ( VcRR2 ). Mu-legacy plants, compared with nontransgenic 'Legacy' plants, show dwarfing, promotion of flower bud formation, and can flower under nonchilling conditions. We conducted transcriptomic comparisons in leaves, chilled and nonchilled flowering buds, and late-pink buds, and analyzed a total of 41 metabolites of six groups of hormones in leaf tissues of both Mu-legacy and 'Legacy' plants. These analyses uncovered that increased VcRR2 expression promotes the expression of a homolog of Arabidopsis thaliana ENT-COPALYL DIPHOSPHATE SYNTHETASE 1 ( VcGA1 ), which induces new homeostasis of hormones, including increased gibberellin 4 (GA4) levels in Mu-legacy leaves. Consequently, increased expression of VcRR2 and VcGA1, which function in cytokinin responses and gibberellin synthesis, respectively, initiated the reduction in plant height and the enhancement of flower bud formation of the Mu-legacy plants through interactions of multiple approaches. In nonchilled flower buds, 29 differentially expressed transcripts of 17 genes of five groups of hormones were identified in transcriptome comparisons between Mu-legacy and 'Legacy' plants, of which 22 were chilling responsive. Thus, these analyses suggest that increased expression of VcRR2 was collectively responsible for promoting flower bud formation in highbush blueberry under nonchilling conditions. We report here for the first time the importance of VcRR2 to induce a suite of downstream hormones that promote flowering in woody plants.